Product formulas for weight two newforms - Nikdelan, Younes; Movasati, Hossein (Cadernos do IME - Série Matemática, 2020)
For a weight two newform $f$ attached to an elliptic curve $E$ defined over rational numbers we write $f=q\prod_{n=1}^∞ (1-q^n)^{g_n}, \ g_n\in \mathbb{Z}$ and we observe that for some special elliptic curves $g_n$ is an increasing sequence of positive integers.